Modern art - Dempsey, Amy, 1963- (Art essentials., 2018)
Amy Dempsey unravels the all-too-often daunting language of modern art by mapping the styles, schools and movements that help us understand modern and contemporary art, from Impressionism in the 19th century to Destination Art in the 21st. Using a practical and easy-to-navigate structure, Dempsey's lucid writing and carefully selected artworks define sixty-eight essential groupings in western modern art.